1996
DOI: 10.1038/bjc.1996.145
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for intellectual and educational sequelae of cranial irradiation in childhood acute lymphoblastic leukaemia

Abstract: Summary Long-term cognitive and educational sequelae have been inconsistently reported in children who received cranial irradiation (CRT) to prevent central nervous system (CNS) disease in acute lymphoblastic leukaemia (ALL). This study investigates a large and representative sample of survivors of ALL and compares them with non-irradiated survivors of cancer and healthy control children to determine the effect of CRT on cognitive and educational ability. Three groups of children were studied: Group 1 (n= 100)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
57
1
5

Year Published

1998
1998
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(66 citation statements)
references
References 28 publications
3
57
1
5
Order By: Relevance
“…Intellectual outcomes were generally better for children treated with 1,800 cGy than 2,400 cGy [Moore et al, 1991;Halberg et al, 1992;Smibert et al, 1996], although this was not a consistent finding Rodgers et al, 1991;Waber et al, 1995]. Significant correlations have been documented between higher CR dose and lower cognitive performance [Kingma et al, 1993].…”
Section: Cranial Radiationmentioning
confidence: 90%
“…Intellectual outcomes were generally better for children treated with 1,800 cGy than 2,400 cGy [Moore et al, 1991;Halberg et al, 1992;Smibert et al, 1996], although this was not a consistent finding Rodgers et al, 1991;Waber et al, 1995]. Significant correlations have been documented between higher CR dose and lower cognitive performance [Kingma et al, 1993].…”
Section: Cranial Radiationmentioning
confidence: 90%
“…in childhood leukaemia [33], 25 studies are cited that report negative effects of irradiation on cognitive meaAlthough the underlying mechanisms of irradiationinduced neurocognitive dysfunction are not yet fully unsurements. Other studies indicate that children who receive CRT develop impaired visual and verbal memory, derstood, present evidence indicates that CRT may induce neurocognitive dysfunction, younger children being the attention capacity, verbal fluency, and visual discrimination skills, verbal IQ, and reading and spelling [34,35]. most susceptible to these injuries.…”
Section: Effects Of Treatment For Pituitary Tumoursmentioning
confidence: 95%
“…31,[33][34][35][36] Clinical experience involving patients suffering from leukemia who received prophylactic cranial irradiation showed that the incidence of intellectual deficits in patients younger than 6 or 8 years of age was higher than that in older subjects. 35,36 Fortunately, intracranial germinomas usually arise in patients older than 8 years of age. In the current study, only 6 (4%) patients were younger than 8 years of age.…”
Section: Discussionmentioning
confidence: 99%